Ngebabali, The Exclusively of Lampung : The Existence of Nature and Enviromental Conservation Practices Through Traditional Traditions - Syahiib, A Nizam; Sari, Dewi Rafika; Selvira, Selvira; Novriyanti, Novriyanti (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Knowledge and local wisdom of community live closely with biodiversity and forest ecosystems are usually manifested in the form of traditional ceremonial traditions, myths, and cultures. It can be one of the protection biodiversity efforts. However, in globalization era and fragmented habitat of diverse biodiversity, the existence of human-nature relation manifestations needs to be questioned, such as existence of the Ngebabali, peculiar tradition of Lampung Province. This research aims to identifying the existence of Ngababali traditional ceremony and analyzing conservation activities certainin it. This research was conducted in Pekon (village) Kota Besi, Batu Brak District, West Lampung Regency in June-September 2021. The study used a combination of virtual ethnography methods, in-depth interviews with adults until saturated data, and filling out questionnaires on the younger generation to complete the data. The research findings indicate that Ngababali is still being carried out in Pekon Kota Besi. This is a tradition of asking God for prayer and protection after clearing land for the construction of houses and gardens. The perpetrators of this tradition are the people who clear the land for certain purposes. Although Ngebabali is a form to support of land clearing activities, in its implementation, this tradition requires several plant species such as inggu, black sweet potato, black taro, black sugar cane, and others. In addition, there is also an obligation to replant previously existing plant species for those who carry it out. Thus, the existence of Ngebabali can indirectly preserve the variety of plant species used.